Platelet Indices: Predicting Retinopathy in Patients with Type 2 Diabetes Mellitus - Arijit Paul; Soumyadip Das; Koushik Bose; Rupam Karmakar (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Diabetes mellitus (T2DM) is a metabolic disorder, characterized by insulin resistance and varying degrees of hyperglycemia, leading to several macrovascular and microvascular complications. In recent years, altered platelet morphology and dysfunctions are reported in patients with T2DM. Platelet indices, namely plateletcrit (PCT), mean platelet volume (MPV), and platelet distribution width (PDW), can predict altered platelet morphology and dysfunction which leads to microvascular complications, such as retinopathy. Aims: This study was aimed at comparing platelet indices in individuals with impaired fasting glucose, T2DM patients, and also in patients with retinopathy; and to determine any association between them. Study Settings, Design, Material, Methods, and Statistical Analysis: A cross-sectional observational study was undertaken on 200 patients attending diabetic OPD of our institution over a period of 18 months. The obtained data were analyzed using suitable statistical software. Results: We found that mean values of platelet indices (MPV, PCT, PDW) are significantly higher in diabetics (11.73 fl, 0.238%, 17.01 fl) than in persons with impaired fasting glucose (9 fl, 0.195%, 11.23 fl). Moreover, they are significantly higher in patients with retinopathy (12.54 fl, 0.257%, 19.05 fl) than in patients without retinopathy (10.21 fl, 0.205%, 13.29 fl). We also found a positive correlation between platelet indices and HbA1C. Conclusion: Platelet indices can easily determine platelet dysfunction and thereby can predict the presence of retinopathy. They may serve as economical and readily available tool in monitoring diabetic patients.